Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fmicb.2017.02593
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Zinc Solubilizing Bacteria in Growth Promotion and Zinc Content of Wheat

Abstract: Zinc is an imperative micronutrient required for optimum plant growth. Zinc solubilizing bacteria are potential alternatives for zinc supplementation and convert applied inorganic zinc to available forms. This study was conducted to screen zinc solubilizing rhizobacteria isolated from wheat and sugarcane, and to analyze their effect on wheat growth and development. Fourteen exo-polysaccharides producing bacterial isolates of wheat were identified and characterized biochemically as well as on the basis of 16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
113
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(145 citation statements)
references
References 59 publications
10
113
0
Order By: Relevance
“…In addition, IAA plays an important role in the regulation of plant abiotic stresses induced by ethylene. Enhancing the availability of plant-utilizable forms of phosphate, iron, potassium and zinc via solubilisation and mobilization by bioinoculants directly increases nutrient availability in soil, thus increasing soil fertility, plant growth, crop productivity and also nutrient content of the grain (Gupta et al, 2015 ; Souza et al, 2015 ; Gopalakrishnan et al, 2016 ; Jegan et al, 2016 ; Kamran et al, 2017 ). The direct and indirect mechanisms of plant growth promotion mediated by strain MSSRFD41 reflect its ability to increase the nutrient content of the seed, soil, and plant biomass.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IAA plays an important role in the regulation of plant abiotic stresses induced by ethylene. Enhancing the availability of plant-utilizable forms of phosphate, iron, potassium and zinc via solubilisation and mobilization by bioinoculants directly increases nutrient availability in soil, thus increasing soil fertility, plant growth, crop productivity and also nutrient content of the grain (Gupta et al, 2015 ; Souza et al, 2015 ; Gopalakrishnan et al, 2016 ; Jegan et al, 2016 ; Kamran et al, 2017 ). The direct and indirect mechanisms of plant growth promotion mediated by strain MSSRFD41 reflect its ability to increase the nutrient content of the seed, soil, and plant biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of organic acids, such as 5-ketogluconic acid and pentanoic acid, by bacteria is associated with acidification of soil or medium and subsequent solubilization of ZnCO 3 (Saravanan et al, 2007). Indeed, Zn-solubilizing bacteria belonging to different genera of the Enterobacteriaceae family have been shown to promote the growth and Zn content of cotton (Kamran et al, 2017). The genes for the production of gluconic acid from glucose (gcd) and subsequent conversion to 5-ketogluconic acid (ghrB) were present in JZ38 ( Supplementary Table S20) (De Muynck et al, 2007).…”
Section: Plant Growth Promoting Traits and Potential For Growth Promomentioning
confidence: 99%
“…Similarly, several Zn solubilizing bacteria (ZSB) including P. fragi, Pantoea dispersa, P. agglomerans, E. cloacae, and Rhizobium sp. isolated from wheat and sugarcane were recently shown to improve the Zn contents and growth of pot-grown wheat [190]. In another study, Dinesh et al [191] several promising ZSB isolated from soil were evaluated for their effects on soil Zn release rates, soil-available Zn and plant Zn contents in a greenhouse experiment and the results showed that Zn concentration in soil and plants was higher in the treated plants than the non-treated controls.…”
Section: Zinc Solubilizersmentioning
confidence: 99%